Teachers’ Challenges in Teaching English to Young Learners in Rural Area - Nadhilla Sekar Pramesty; Ana Maghfiroh; Diyah Atiek Mustikawati (STAI Hubbulwathan Duri, 2022)
It is believed that rural education has unique challenges compared to urban and suburban areas, particularly in teaching English to young learners. Problems that often occur are related to educational inequality for those who live in rural areas, such as unqualified teachers, limited educational facilities, or lack of parental support. This study aims to identify the challenges faced by English teachers and their strategies in teaching English to young students in rural areas. This qualitative research used direct observation in the classroom and interviews with the English teacher an elementary school in Ponorogo. The findings showed that (1) learning English in remote areas was constrained by the status of English as a local content that created less supportive conditions for teachers to teach English; (2) most of the teachers came from non-English educational backgrounds, which affected their competence; (3) the learning curriculum was not in accordance with the existing learning conditions; and (4) the socioeconomic status of parents had a significant effect on students' motivation and achievement in learning English. Therefore, English teachers in rural areas need to use various strategies to address the mentioned problems.